Upaya Pengelolaan Sampah di Pusat Daur Ulang Sampah KSM â€œManunggal Berkahâ€ Lugosobo - Ana Tri Lestari; Dwi Nursanti; Rosita Rahmawati; Nur Ngazizah (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The waste management process at this recycling center involves separating waste that can be recycled and what cannot. The research results show that waste recycling centers provide significant benefits to the community. The environment is cleaner, and these efforts provide real help to the community. Additionally, recycling centers provide employment opportunities to employees, especially those who may not have previously had a job, thereby helping to improve their economic conditions. The Lugosobo waste recycling center not only plays a role in waste management, but also provides support for the environment and local economy. This research uses qualitative methods with descriptive analysis techniques through literature study, focusing on describing phenomena that exist or have occurred. Data was obtained from various sources such as interviews, field notes, audio recordings, videos and documentation. This research reviews the KSM